Early Development of Fig (Ficus carica L.) Root and Shoot Using Different Propagation Medium and Cutting Types - Muhammad Syufihuddin Shamsuddin; Rozilawati Shahari; Che Nurul Aini Che Amri; Nur Shuhada Tajudin; Mohd. Radzali Mispan; Mohd Syahmi Salleh (Tropical Life Sciences Research, 2021)
This study aimed at determining the effects of propagation medium and cutting types on the early growth performance of fig (Ficus carica L.) root and shoot. The experiment was conducted at the Glasshouse and Nursery Complex (GNC), International Islamic University Malaysia (IIUM). The split-plot design was employed with the main plot (propagation medium) and sub-plot (types of cutting). The propagation medium were sand + topsoil (1:3) (M1), topsoil + peat + sawdust (1:1:1) (M2) and peat + perlite (1:1) (M3). Two types of cutting were semi-hardwood (C1) and hardwood (C2). As a result, there were a significant effect of propagation medium on measured parameters. This study revealed that the most effective propagation medium and cutting types for the propagation of fig were a combination of peat and perlite at 1:1 ratio (M3) and hardwood cutting (C2), respectively as evidenced by significantly higher root and shoot growth quality as compared to other treatments.